Joining of Fibre-Reinforced Thermoplastic Polymer Composites by Friction Stir Welding—A Review - Pereira, Miguel A. R. (2022)
The objective of the current work is to show the potential of the friction stir welding (FSW) and its variants to join fibre-reinforced thermoplastic polymer (FRTP) composites. To accomplish that, the FSW technique and two other important variants, the friction stir spot welding (FSSW) and the refill friction stir spot welding (RFSSW), are presented and explained in a brief but complete way. Since the joining of FRTP composites by FSSW has not yet been demonstrated, the literature review will be focused on the FSW and RFSSW techniques. In each review, the welding conditions and parameters studied by the different authors are presented and discussed, as well as the most important conclusions taken from them. About FSW, it can be concluded that the rotational speed and the welding speed have great influence on heat generation, mixture quality, and fibre fragmentation degree, while the tilt angle only has residual influence on the process. The reduction of internal and external defects can be achieved by adjusting axial force and plunge depth. Threaded or grooved conical pins achieved better results than other geometries. Stationary shoulder tools showed better performance than conventional tools. Regarding the RFSSW, it has not yet been possible to deepen conclusions about most of the welding parameters, but its feasibility is demonstrated.